Identification of Phytophthora species by a high resolution melting analysis: An innovative tool for rapid differentiation - Antonios Zambounis (2018)
© 2016, Czech Academy of Agricultural Sciences. All rights reserved. A new molecular method via the high resolution melting (HRM) analysis of the Ypt1 gene non-coding regions was validated for ten Phytophthora species with a broad host range from forest trees to crop species. The melting curve analysis of the amplicons specifically grouped all species into 10 respective unique and distinct HRM curve profiles. The analysis of the normalised HRM melting curves, assigning P. nicotianae as a normalised reference genotype, revealed that the genotype similarities among all the species were adequately low, indicating that Ypt1 marker was sufficient to identify and differentiate the tested species. This HRM method is rapid and reproducible allowing the identification of Phytophthora species and the screening of eventual variants eliminating the separate steps and reducing the risk of contamination.